Problematika uživanja pogosto preučevanih antioksidantov v obliki prehranskih dopolnil - Jakše, Boštjan (Šport (Ljubljana), 2019)
Use of dietary supplements has become so widespread due, at least to some extent, to the belief that they help prevent common modern chronic diseases. The results of a number of older observational studies showed that nutrition which is based on higher intake of fruit and vegetables is associated with lower risk of many types of cancer, including respiratory and gastrointestinal cancers. Many researchers thus concluded that taking antioxidants in the form of dietary supplements can similarly improve a person's health and potentially prolong their life. More accurately, consumption of antioxidants in the form of dietary supplements can potentially prevent some types of cancer, cardiovascular diseases, other chronic diseases and premature death in healthy and ill population suffering from frequent chronic diseases. In the case of repeated and strenuous physical effort as well as very active individuals and athletes, consumption of antioxidants in the form of dietary supplements is said to contribute to effective post-exercise regeneration or successful sport performance as well as strengthen athletes' immune system. In the past two decades, many independent researchers have analysed different randomly controlled studies, which differed in terms of concept and methodology, while also considering the potential impact of a conflict of interest. In both patients and healthy study subjects, research results showed favourable, neutral and many times even unfavourable results of consuming antioxidants in the form of dietary supplements, especially when intake exceeded the recommended dose. The purpose of the article is to answer the topical consumer question about potential benefits or risks of consuming frequently studied, advertised and sold antioxidants in the form of dietary supplements, such as, for example, beta carotene and vitamins E, A and C. We will focus primarily on reviews of randomly controlled studies of this topic as well as on responses of other scientists and of the dietary supplement industry on the results of some study reviews.
Keywords: antioksidanti; antioxidants; chronic diseases; dietary supplements; healthy lifestyle; kronične bolezni; prehranska dopolnila; prevention; preventiva; sport; šport; zdrav življenjski slog